High-strength galvanized steel sheet having excellent electrical resistance spot weldability and method for manufacturing the same
Patent Information
- Application Number
- JP2023192741
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-12-19
- Filing Date
- 2023-11-13
- Publication Date
- 2025-02-25
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a high-strength galvanized steel sheet with excellent electric resistance spot weldability and a method for manufacturing the same. Regarding. [Background technology]
[0002] Due to issues such as environmental pollution, regulations on automobile exhaust gases and fuel efficiency are becoming increasingly strict. This has led to increased demand for lighter steel sheets in automobiles to reduce fuel consumption. In response to this demand, various high-strength steel plates with high strength per unit thickness have been developed. It is now commercially available.
[0003] High strength steel usually means steel with a strength of 490 MPa or more, but this does not necessarily mean The present invention is not limited to the above, but includes transformation induced plasticity (TIP). ed Plasticity;TRIP) steel, Twin Induced Plasticity Plasticity (TWIP) steel, Dual Phase (DP) steel, Complex Phase (CP) steels and the like fall into this category.
[0004] On the other hand, the steel materials used in automobiles are made of plated steel sheets, which have a plated surface to ensure corrosion resistance. They are supplied in the form of zinc-coated steel sheets (GI steel sheets) or alloyed zinc-coated steel sheets. (GA) has high corrosion resistance due to the sacrificial corrosion protection properties of zinc, and is therefore used as an automotive material. It is widely used.
[0005] However, when the surface of high-strength steel plate is plated with zinc, it is said that spot weldability decreases. That is, high-strength steel has a high yield strength as well as a high tensile strength, so It is difficult to eliminate the tensile stress caused by firing deformation, and microcracks appear on the surface. When high-strength galvanized steel sheets are welded, the zinc, which has a low melting point, melts into the steel. The metals penetrate into the microcracks in the plate, resulting in liquid metal embrittlement. This causes a phenomenon called lateral embrittlement (LME), which leads to the destruction of the steel plate. This is a major obstacle to increasing the strength of steel plates. It is being used.
[0006] In addition, high-strength steel sheets contain alloying elements such as Mn, Al, and Si that react with the atmosphere. The reaction forms an oxide on the surface of the steel sheet, but in this case, the coating adhesion is greatly reduced. However, problems may occur in the surface quality of the plated steel sheet. Summary of the Invention [Problem to be solved by the invention]
[0007] According to one aspect of the present invention, a galvanized steel sheet having excellent spot weldability and a method for producing the same are provided. Provided.
[0008] The subject of the present invention is not limited to the above. A person having knowledge of the present invention can easily understand the addition of the present invention from the contents described throughout the specification of the present invention. There is no difficulty in understanding the objective problem. [Means for solving the problem]
[0009] According to one aspect of the present invention, a galvanized steel sheet includes a base steel sheet and a galvanized layer formed on the top of the base steel sheet. and a zinc-based coating layer, the surface of the base steel sheet being represented by the following formula 1: The decarburization rate of the layer can be 30% or more.
[0010] [Formula 1] Decarbonization rate of surface layer (%) = (1-average carbon concentration of surface layer / bulk carbon concentration)*100
[0011] Here, the surface layer refers to a region from the surface of the base steel sheet to a depth of 35 μm.
[0012] According to another aspect of the present invention, a method for producing a galvanized steel sheet includes hot rolling a steel slab. A step of obtaining a steel sheet, and coiling the hot-rolled steel sheet at a temperature of 590 to 750°C to obtain a hot-rolled steel sheet. The edge of the coiled hot-rolled steel sheet is then heated in a nitrogen atmosphere containing 0.5 to 2% oxygen. and heating the hot-rolled steel sheet at 600 to 800°C for 5 to 24 hours. and passing the cold rolled steel sheet at a speed of 40 to 130 mpm while passing the sheet at 650 annealing the cold-rolled steel sheet at 900°C or higher in an atmosphere with a dew point of -10 to 30°C; and hot-dip galvanizing the steel sheet. Effect of the Invention
[0013] As described above, the present invention provides a method for forming a decarburized layer in the surface layer of the base steel immediately below the coating layer, Zinc plating with excellent surface quality and excellent LME resistance during resistance spot welding. It is possible to produce steel plates. [Brief description of the drawings]
[0014] [Figure 1] 1 is a graph showing an interval for performing integration on a carbon concentration profile in order to measure the degree of decarbonization. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below.
[0016] In the present invention, the galvanized steel sheet includes not only galvanized steel sheet (GI steel sheet) but also alloy steel sheet. This includes not only galvanized steel sheets (GA) but also any plated steel sheets that contain zinc as a main component. It is important to keep in mind that this is a concept. The fact that zinc is the main component means that the plating layer This means that the proportion of zinc is the highest among all elements contained in zinc alloy. In coated steel sheets, the proportion of iron can be higher than that of zinc, and the remaining components other than iron are It may include having the highest percentage.
[0017] The inventors of the present invention have discovered that the cause of liquid metal embrittlement (LME) that occurs during welding is the surface of the steel plate. In order to suppress microcracks on the surface, we focused on the fact that the cause is microcracks that occur from the surface. As a result of research into the means of achieving this, it was found that it was necessary to soften the surface of the steel plate. This finding led to the development of the present invention.
[0018] Normally, high strength steels contain C, M, etc. to ensure the hardenability and austenite stability of the steel. They may contain large amounts of elements such as n, Si, Cr, Mo, and V. These elements are Therefore, steels containing large amounts of these elements Microcracks are easily generated in the steel, which may result in liquid metal embrittlement during welding. According to the results of their research, the occurrence of such microcracks is closely related to the carbon concentration. Since cracks occur from the surface and propagate to the inside, when the carbon concentration on the surface is high, The possibility of microcracks occurring increases.
[0019] Therefore, in one embodiment of the present invention, the overall composition of the steel is high carbon for high strength. The carbon concentration in the surface layer, where cracks occur, is adjusted to a level that is To have a low carbon concentration, i.e., a high decarburization rate, so as to have resistance to cracking. do.
[0020] In the present invention, the surface layer portion refers to a point within 35 μm in the depth direction from the surface of the steel sheet. The decarburization rate of the surface layer can be expressed by the following equation [1].
[0021] [Formula 1] Decarbonization rate of surface layer (%) = (1-average carbon concentration of surface layer / bulk carbon concentration)*100
[0022] In the above formula 1, the carbon concentration in the surface layer means the average carbon concentration in the surface layer, and The carbon GDS (a concept that includes any similar instruments such as GDOES) program shown In the file, the integrated value from the surface layer of the base steel plate to a depth of 35 μm is used as the depth (35 μm ) The bulk carbon concentration can be expressed as the value divided by the This means the carbon concentration at which there is no further change in carbon concentration even when moving in the depth direction. This means the carbon concentration at 1 / 4 of the plate thickness. The degree of cracking can be obtained by removing a portion of the steel sheet in the depth direction and then performing a GDS analysis.
[0023] In one embodiment of the present invention, the decarbonization rate of the surface layer is based on a value measured at the center in the width direction. However, in general, the edge portion in the width direction of the steel plate is more susceptible to cracking than the center portion in the width direction. Since the decarburization rate at the edge portion is often higher than the value specified in the present invention, When the above condition is satisfied, the spot weldability can be further improved. The "parts" refer to both end points of the cross section of the steel plate cut in the width direction. If there is a problem with the soundness of the test piece, such as the edge being damaged, the test piece should be cut 1 mm inward in the width direction from the edge point. It can mean a point.
[0024] As described above, in one embodiment of the present invention, sufficient spot by preventing the occurrence of LME In order to ensure weldability, the decarburization rate may be 30% or more. According to an embodiment, the decarburization rate is 40% or more, and in yet another embodiment, the decarburization rate is can be 50% or more.
[0025] Since the higher the decarburization rate, the more advantageous it is, there is no need to set an upper limit to the decarburization rate. According to one embodiment of the present invention, the upper limit of the decarburization rate can be 90%, and in other embodiments, In one embodiment, the upper limit of the decarburization rate can be 80%, and in another embodiment, The upper limit of the decarburization rate can be set at 70%.
[0026] According to one embodiment of the present invention, an internal oxide may be present in the surface layer of the base steel sheet. The inner oxide contains at least one of Si, Mn, Al, and Fe. In addition, the steel sheet may further contain additional elements derived from the composition of the base steel sheet.
[0027] The steel plate covered by this invention is a high-strength steel plate with a strength of 490 MPa or more, regardless of the type. However, although not necessarily limited thereto, the steel sheet to which the present invention is directed is By weight, C: 0.05-1.5%, Si: 2.0% or less, Mn: 1.0-30%, S -Al (acid-soluble aluminum): 3% or less, Cr: 2.5% or less, Mo: 1% or less, B :0.005% or less, Nb:0.2% or less, Ti:0.2% or less, V:0.2% or less, S It may have a composition including b+Sn+Bi: 0.1% or less, and N: 0.01% or less. The remaining components are iron and other impurities, as well as any other elements not listed above and present in the steel. However, the present invention does not exclude the inclusion of further elements that may be contained within a range of 1.0% or less in total. In the above, the content of each component element is expressed on a weight basis unless otherwise specified. The composition of the steel sheet refers to the bulk composition of the steel sheet, that is, the composition at the 1 / 4 point of the steel sheet thickness (hereafter, Below, same).
[0028] However, in some embodiments of the present invention, the high strength steel plate is TRIP steel or the like. Each steel may have the following composition:
[0029] Steel composition 1: C: 0.05-0.30% (preferably 0.10-0.25%), Si: 0 0.5-2.5% (preferably 1.0-1.8%), Mn: 1.5-4.0% (preferably 2.0~3.0%), S-Al: 1.0% or less (preferably 0.05% or less), Cr: 2 0.0% or less (preferably 1.0% or less), Mo: 0.2% or less (preferably 0.1% or less) ), B: 0.005% or less (preferably 0.004% or less), Nb: 0.1% or less (preferably or 0.05% or less), Ti: 0.1% or less (preferably 0.001 to 0.05%), Sb+Sn+Bi: 0.05% or less, N: 0.01% or less, balance Fe and unavoidable impurities In some cases, elements not listed above that may be contained in steel may be contained in a total amount of 1.0% or less. It can further include a range of up to.
[0030] Steel composition 2: C: 0.05-0.30% (preferably 0.10-0.2%), Si: 0. 5% or less (preferably 0.3% or less), Mn: 4.0 to 10.0% (preferably 5.0 to 9.0%), S-Al: 0.05% or less (preferably 0.001 to 0.04%), Cr: 2.0% or less (preferably 1.0% or less), Mo: 0.5% or less (preferably 0.1 to 0 .35%), B: 0.005% or less (preferably 0.004% or less), Nb: 0.1% or less below (preferably 0.05% or less), Ti: 0.15% or less (preferably 0.001 to 0. 1%), Sb+Sn+Bi: 0.05% or less, N: 0.01% or less, balance Fe and unavoidable Impurities are included. In some cases, elements not listed above that may be contained in steel may be included in the total of 1. It may further include a range of up to 0%.
[0031] In addition, when the lower limit of the content of each of the above-mentioned component elements is not specified, they are arbitrary. This means that it may be an arbitrary element and its content may be 0%.
[0032] According to one embodiment of the present invention, the surface of the steel sheet includes one or more plating layers. The above plating layer is GI (Galvanized) or GA (Galva-an In the present invention, the above-mentioned zinc-based plating layer may be a zinc-based plating layer including a zinc-based plating layer such as ... Since the ratio of Ceq is appropriately controlled, even if a zinc-based coating layer is formed on the surface of the steel sheet, the This helps to reduce the problem of liquid metal embrittlement that occurs during pot welding.
[0033] When the zinc-based coating layer is a GA layer, the degree of alloying (meaning the content of Fe in the coating layer) is The content of the alloy (which has a taste) can be controlled to 8 to 13% by weight, preferably 10 to 12% by weight. If the degree of oxidation is insufficient, the zinc in the zinc-based plating layer will penetrate into the microcracks and become liquid gold. On the other hand, if the alloying degree is too high, problems such as powdering may occur. What problems might occur?
[0034] The coating weight of the zinc-based coating layer is 30 to 70 g / m 2 It can be. If the plating weight is too low, it is difficult to obtain sufficient corrosion resistance. If the amount of adhesion is too large, the manufacturing cost may increase and problems of liquid metal embrittlement may occur. Therefore, the coating weight is controlled within the above range. A more preferable range of the coating weight is 40 to 60 g / g. m 2 The plating weight means the amount of the plating layer attached to the final product. When the plating layer is a GA layer, the plating weight increases due to alloying. Therefore, the weight may be slightly reduced before alloying. Although not necessarily limited thereto, the coating weight before alloying (i.e., the amount of coating from the plating bath) The amount of plating applied may be reduced by about 10%.
[0035] Hereinafter, an embodiment of the method for producing the steel sheet of the present invention will be described. The steel sheet of the present invention does not necessarily have to be manufactured according to the following embodiment, and the following embodiment may be used as the steel sheet of the present invention. It should be noted that this is one preferred method of manufacture.
[0036] First, a steel slab having the above-mentioned composition is hot-rolled and then coiled to produce a hot-rolled steel sheet. It is possible to produce slabs by heating (temperature control in case of direct rolling) or by hot rolling. Although the conditions are not particularly limited, in one embodiment of the present invention, the winding temperature is set as follows: can be restricted.
[0037] Winding temperature: 590~750℃ The hot-rolled steel sheet is later wound up in coil form and stored. The plate undergoes a slow cooling process. This process causes the oxidation of the surface layer of the plate to However, if the coiling temperature of the slab is too low, these elements are removed by oxidation. The coil is cooled slowly at a temperature lower than the required temperature, making it difficult to achieve a satisfactory effect. Conversely, if the winding temperature is too high, the temperature deviation between the center and the edge in the width direction will be This increases the material deviation. In this case, the cold rolling property deteriorates. In addition, the strength of the final product may decrease, and the moldability may also become poor. From the viewpoint of oxidation, if the coiling temperature is too high, re-oxidation of scale occurs, resulting in Fe 2 O 3 However, this may result in poor surface quality. In one embodiment of the present invention, the upper limit of the winding temperature can be set to 750°C.
[0038] Heating the edges of hot rolled coils: 600-800℃ for 5-24 hours In one embodiment of the present invention, in order to increase the decarburization rate of the edge portion, the edge portion of the hot rolled coil is The edge heating of the hot rolled coil is performed by heating both ends of the coil in the width direction. In other words, this means heating the edge portion, which causes the edge portion to oxidize. The coil is first heated to a suitable temperature. That is, the coil is wound and its inside is kept at a high temperature. However, the edges cool relatively quickly, thus maintaining a temperature suitable for internal oxidation. Therefore, the time that the edge is held is shorter than that in the center of the width direction. The removal of oxidizing elements at the edge is not as active. Heating the edge reduces the amount of oxidizing elements at the edge. This can be used as one of the methods to remove elements.
[0039] That is, when the edge portion is heated, the edge portion is heated in the opposite manner to the cooling after winding. This allows the temperature of the edge in the width direction to be maintained at a temperature suitable for internal oxidation. However, as a result, the thickness of the internal oxide layer at the edge portion increases. The heating temperature of the edge part must be 600°C or higher (based on the temperature of the steel plate edge part). However, if the temperature is too high, excessive scale may form on the edge during heating. The surface condition after pickling is poor because of the formation of porous high-oxidation scale (hematite). The temperature of the edge portion may be set to 800° C. or less. A more preferable heating temperature for the edge portion is 600 to 750°C.
[0040] In addition, the unevenness of the surface layer Ceq value between the edge and center in the width direction that occurred during winding was corrected. To solve this problem, the heating time for the edge portion must be 5 hours or more. If the heating time for the edge part is too long, excessive scale may form or the surface of the edge part may deteriorate. The decarburization rate of the layer may become excessively high. Therefore, the heating time of the edge is set to 24 hours. The time can be less than or equal to the time.
[0041] According to an embodiment of the present invention, the edge portion is heated by a combustion heating method by adjusting the air-fuel ratio. In other words, the oxygen fraction in the atmosphere is changed by adjusting the air-fuel ratio. However, the higher the oxygen partial pressure, the higher the oxygen concentration in contact with the surface layer of the steel sheet, and the more likely it is that decarburization and internal oxidation will occur. Although not necessarily limited thereto, one embodiment of the present invention may In this configuration, the air-fuel ratio is adjusted to control the nitrogen atmosphere containing 0.5 to 2% oxygen by volume. It is possible for a person having ordinary skill in the art to which the present invention pertains to have no particular difficulty in The oxygen fraction can be controlled by adjusting the air-fuel ratio without affecting the combustion efficiency. No explanation will be given.
[0042] After the above process, the hot-rolled steel sheet is pickled as necessary and then cold-rolled. The above-mentioned cold rolling process may be followed by a process of annealing the steel sheet. The decarburization rate of the surface layer can change significantly during the annealing process of the steel sheet. The annealing process can be controlled under conditions that appropriately control the decarburization rate of the surface layer, among which: The strip threading speed and the dew point in the annealing furnace can be controlled to the following conditions.
[0043] Threading speed: 40~130mpm In order to ensure sufficient productivity, the threading speed of the above cold-rolled steel sheets must be 40 mpm or more. However, if the threading speed is too fast, it is disadvantageous in terms of securing the quality of the material. In one embodiment, the upper limit of the threading speed may be 130 mpm. The speed affects the thickness of the internal oxide layer. The slower the strip speed, the thicker the internal oxide layer becomes. The thickness of the strip increases and the carbon content decreases. This may cause the thickness of the partial oxide layer to be insufficient. At a strip running speed exceeding 1.0 m, an internal oxide layer may be formed with a thickness of 3 μm or less.
[0044] Annealing conditions: 650 to 900°C and -10 to 30°C dew point atmosphere. The annealing temperature in the present invention is 650°C or higher, which is a temperature at which sufficient internal oxidation effect is achieved. However, if the temperature is too high, surface oxides of silicon and other substances are formed, Not only does it prevent oxygen from diffusing inward, but it also prevents the austenite from overforming during heating in the soaking zone. This may occur frequently, slowing down the carbon diffusion rate and thus reducing the degree of decarburization. This causes a load on the annealing furnace, shortening the equipment life and increasing the process cost. Therefore, the temperature at which the dew point is controlled must be 900°C or lower. In the present invention, the temperature at which annealing is performed means the temperature of the soaking zone.
[0045] At this time, in order to form a sufficient and uniform internal oxide layer, the dew point of the atmosphere in the annealing furnace is controlled. If the dew point is too low, surface oxidation will occur instead of internal oxidation. Therefore, the dew point is -10℃. Conversely, if the dew point is too high, oxidation of Fe may occur. Therefore, the dew point must be controlled to 30°C or less.
[0046] In this case, the dew point is measured by measuring the dew point of wet nitrogen (N 2 +H 2 O) is placed in the annealing furnace. It can be adjusted by doing so.
[0047] The steel sheet annealed by this process is immediately immersed in a plating bath for hot-dip galvanizing. conduct.
[0048] Steel sheets annealed in this way must be heated to a temperature above the plating bath temperature (460 to 500°C). After heating, the steel sheet is immersed in a plating bath to perform hot-dip galvanizing. The thickness of the annealed steel sheet immersed in the plating bath can be adjusted to 1.0~2.0mm. According to one embodiment of the present invention, the plating bath is a zinc-based plating bath, and contains 50% Zn. It may contain 50% by weight or more.
[0049] Alloying (GA) temperature: 480~560℃ Below 480℃, the amount of Fe diffusion is small and the degree of alloying is insufficient, resulting in poor plating properties. If the temperature exceeds 560℃, powdering may occur due to excessive alloying. Powdering problems may occur due to the presence of residual austenite in the ferrite. Since the alloying temperature is set within the above-mentioned range, the material may be deteriorated due to the alloying transformation.
[0050] In one embodiment of the present invention, in order to ensure the sufficient degree of alloying, the alloying heat The treatment time can be 1 second or more. However, if the alloying heat treatment time is too long, Since the degree of alloying may exceed the range specified in the present invention, the alloying heat treatment time may be extended. The limit may be five seconds. EXAMPLES
[0051] The present invention will be described in more detail below with reference to examples. However, the following examples are merely illustrative of the present invention. The above description is merely for illustrative purposes and is not intended to limit the scope of the present invention. It should be noted that the scope of the present invention is limited to the matters described in the claims. and is determined by matters that can be reasonably inferred therefrom.
[0052] (Example) Steel slabs having the composition shown in Table 1 below (the remaining components not shown in the table are Fe and These are unavoidable impurities. In the table, B and N are shown in ppm, and the remaining After hot rolling, the hot rolled coil is subjected to nitrogen treatment containing oxygen. The edges are heated in a 0.25% atmosphere, then pickled, and the resulting cold-rolled steel sheet is annealed in an annealing furnace. Then, the steel sheet was reheated to 480°C and immersed in a zinc-based plating bath containing 0.13% by weight of Al. The obtained hot-dip galvanized steel sheet was subjected to hot-dip galvanizing as required. The galvannealed (GA) heat treatment was then performed for 4 seconds to finally obtain a galvannealed steel sheet.
[0053] In addition, when a hot-dip galvanized steel sheet is obtained without alloying, the above-mentioned cold-rolled steel sheet is annealed. After annealing and reheating in a furnace, the steel was immersed in a zinc-based plating bath containing 0.24% by weight of Al and plated. Then, the steel sheet is cooled after the air knife and finally the hot-dip galvanized (GI) steel sheet is obtained. Got it.
[0054] In all examples, the reduction rate during cold rolling was 52%, and the soaking temperature during annealing was 830°C. The ratio of hydrogen contained in the wet nitrogen in the annealing furnace was 5.0% by volume. The conditions for each example are as shown in Table 2 (in the table, B and N are shown in ppm). , the remaining ingredients are expressed in weight percent).
[0055] [Table 1]
[0056] [Table 2]
[0057] The properties of the galvannealed (GA) steel sheets manufactured by the above process were measured, and the spots were Table 3 shows the results of observing whether or not liquid metal embrittlement (LME) occurred during hot welding. The steel plate was cut in the width direction, and spot welding was performed along each cut edge. After applying the welding current twice, the hold time is maintained for one cycle. Spot welding was performed in three layers of two types. The 4t materials were stacked in order and spot welded. When spot welding, a new electrode was inserted into the soft material. After welding 15 times at 1000m, the electrode was worn down and the spot welding material was dissipated. After measuring the upper limit current, the upper limit current was set at 0.5 and 1 Spot welding was performed 8 times for each welding current at a current lower than .0kA, and the cross section of the spot weld was discharged. After machining to a high degree of precision, the specimen is epoxy mounted and polished, and then examined under an optical microscope. When observing with an optical microscope, the magnification was set to 100x. If no cracks are found, it is determined that liquid metal embrittlement has not occurred. If spot welds were found, their lengths were measured using image analysis software. B-type cracks occur when the crack size is less than 100μm, and C-type cracks occur when the crack size is less than 100μm. was judged to be good when no abnormality was observed.
[0058] The decarbonization rate was calculated using the concentration values of the components at each depth by GDOES. The decarburization rate was calculated using Equation 1 as described above. The tensile strength was calculated using the C-direction tensile strength of the JIS-5 standard. The alloying degree and plating weight were measured using a hydrochloric acid solution. The sealer adhesion was measured using the wet dissolution method. After bonding to the plated surface, the steel plate was bent 90 degrees to check whether the plating would come off. The ring is made by bending the plated material 90 degrees, attaching tape to the bent area, and then peeling it off. The tape was used to measure how many millimeters of plated layer could be removed. Flaking After processing into a U-shape, it was confirmed whether the plating layer fell off at the processed portion.
[0059] [Table 3]
[0060] Inventive Examples 1, 2, 3, 4, 5, 6, 7, 8, and 9, the composition of the steel is within the range proposed by the present invention. The manufacturing method also satisfies the scope of the present invention, and the tensile strength, plating quality, plating adhesion, The length of the LME crack during spot welding was also good.
[0061] In Comparative Example 1, the alloying temperature during the GA alloying process was controlled to be lower than the range proposed in the present invention. As a result, the alloying degree is lower than the standard, the surface is too bright, and the surface quality is poor. The quality was poor, and flaking occurred, resulting in poor plating surface quality.
[0062] In Comparative Example 2, the heating time during the heat treatment of the edge portion exceeded the range specified in the present invention. In this case, overoxidation occurs at the edge during the heat treatment process, causing the surface scale to turn red. Hematite scale formed and the thickness of the scale became excessive. During the pickling process after hot rolling, the edges are excessively pickled, resulting in high surface roughness and poor plating. Later, the surface shape was uneven and the color of the surface was different from the center, resulting in a color unevenness defect. .
[0063] Comparative Example 3 is a case where the coiling temperature during the hot rolling process was higher than the range proposed by the present invention. Therefore, the decarburization that occurs during the hot rolling process occurs sufficiently, and the dew point during annealing is increased. The decarburization rate of the surface layer is 40% or more, and the plating surface quality and LME resistance are excellent. However, there was a deviation in the material quality in the width direction, and the cold rolling property and tensile strength were poor.
[0064] Comparative Example 4 is a case where the heating furnace temperature of the heat treatment furnace exceeds the range proposed in the present invention. During the process, peroxidation occurs at the edges, causing red hematite-based stains on the surface. The scale formed and the thickness of the scale became excessively thick. In addition, the edging was damaged during the pickling process after hot rolling. The surface roughness increases due to excessive pickling of the sintered parts, and the surface shape becomes uneven after plating. In this case, a defect of uneven hue occurred in which the surface color was different from the center.
[0065] Comparative Example 5 is a case where the coiling temperature during the hot rolling process was controlled to be lower than the range proposed by the present invention. Therefore, the decarburization that occurs during the hot rolling process does not occur sufficiently, resulting in poor LME properties. was.
[0066] In Comparative Examples 6 and 13, the dew point in the furnace during annealing was lower than the range proposed by the present invention. Even if a sufficient decarburized layer is generated over the entire width during the hot rolling and heating processes in the heat treatment furnace, The dew point during the annealing process is not high enough to homogenize the carbon and form a sufficient level of decarburization. The length of the LME crack during spot welding was poor across the entire width. The dew point is too low to allow sufficient internal oxidation, resulting in excessive surface oxidation and The adhesion was poor.
[0067] In Comparative Example 7, the steel sheet passing speed in the annealing furnace was lower than the range proposed in the present invention. The time given for the decarburization reaction between the steam in the annealing furnace and the steel sheet is sufficient, and the steel sheet is The criteria are met when evaluating LME cracks during pot welding, but the manufacturing time is long. The productivity was poor and the manufacturing conditions were not suitable.
[0068] In Comparative Examples 8, 11, and 15, the dew point in the furnace during annealing was controlled higher than the range proposed by the present invention. In this case, decarburization during hot rolling and annealing occurred sufficiently to improve LME resistance. The plating surface quality was good, but the excessive generation of Mn-based oxides caused problems during annealing. Oxides physically adhere to the surface of the hearth roll in the furnace, causing the steel plate to crack. This caused dents, which are depression defects, to be formed in the workpiece, resulting in poor operability.
[0069] In Comparative Example 9, the heating temperature of the heat treatment furnace during the heat treatment of the edge portion was lower than the range of the present invention. This is the case where a sufficient decarburized layer is not formed during hot rolling, and LME cracks occur during spot welding. When evaluated, it did not meet the standards and was found to be defective.
[0070] In Comparative Example 10, the heating temperature and time of the heat treatment furnace are within the ranges set forth in the present invention, but the oxygen During the heat treatment process, over-oxidation occurs at the edge, causing surface scale. The red hematite scale formed on the steel and the thickness of the scale became excessive. In addition, the edge was excessively pickled during the pickling process after hot rolling, resulting in surface roughness. After plating, the surface shape is uneven and the surface color is different from the center. Non-uniform defects occurred.
[0071] In Comparative Example 12, the steel sheet passing speed during the annealing heat treatment was higher than the range proposed by the present invention. This is the case where the time given for the decarburization reaction in which the steam in the annealing furnace reacts with the steel sheet is controlled. As a result, the decarburization rate of the surface layer of the steel sheet is insufficient after annealing, and the L ME cracks occurred exceeding the standard.
[0072] In Comparative Example 14, the heating temperature and time of the heat treatment furnace are within the ranges proposed by the present invention, but the oxygen The hot rolling decarburization layer is not formed sufficiently, and the decarburization rate is lower than the range. When the LME crack was evaluated, it did not meet the criteria and was deemed defective.
[0073] Comparative Example 16 is a case where the alloying temperature in the GA alloying process exceeds the range proposed in the present invention. The high degree of Fe alloying resulted in a dark hue and poor surface quality. During testing, excessive powdering occurred.
[0074] In Comparative Example 17, the heating temperature of the heat treatment furnace satisfies the range of the present invention, but the heating time in the heat treatment furnace This is the case where the time is shorter than the range proposed in the present invention. When evaluating LME cracks during welding, the criteria were not met and the product was found to be defective.
Claims
1. A galvanized steel sheet including a base steel sheet and a zinc-based plating layer formed on an upper portion of the base steel sheet, The decarburization rate of the surface layer of the base steel sheet, which is represented by the following formula 1 at points 1 mm inward in the width direction from both end points of a cross section cut in the width direction of the steel sheet, is 30% or more, The base steel sheet is C: 0.05 to 0.30%, Si: 0.5 to 2.5%, Mn: 2.0 to 3.0%, S-Al: 1.0% or less, Cr: 2.0% or less, Mo: 0.2% or less, B: 0.005% or less, Nb: 0.1% or less, Ti: 0.1% or less, Sb+Sn+Bi: 0.05% or less, N: 0.01% or less, elements not listed above and which may be contained in steel: 1.0% or less in total, the balance being Fe and unavoidable impurities, or 1. A high-strength galvanized steel sheet comprising: C: 0.05 to 0.30%, Si: 0.5% or less, Mn: 4.0 to 10.0%, S-Al: 0.05% or less, Cr: 2.0% or less, Mo: 0.5% or less, B: 0.005% or less, Nb: 0.1% or less, Ti: 0.15% or less, Sb+Sn+Bi: 0.05% or less, N: 0.01% or less, elements not listed above and which may be contained in steel: a total of 1.0% or less, the balance being Fe and unavoidable impurities. [Formula 1] Decarbonization rate of surface layer (%) = (1 - average carbon concentration of surface layer / bulk carbon concentration) * 100 (Note that the surface layer refers to the region from the surface of the base steel sheet to a depth of 35 μm.)
2. A high-strength galvanized steel sheet as described in claim 1, wherein the decarburization rate of the surface layer is 40% or more.
3. A high-strength galvanized steel sheet as described in claim 1, wherein the tensile strength of the base steel sheet is 490 MPa or more.
4. The high-strength galvanized steel sheet according to claim 1, wherein the zinc-based plating layer has a coating weight of 30 to 70 g / m 2 .
5. A high-strength galvanized steel sheet described in any one of claims 1 to 4, wherein the zinc-based plating layer is an alloyed hot-dip galvanized (GA) layer having a degree of alloying, which means the Fe content in the plating layer, of 8 to 13 weight %.